Emerging Lipid based Systems for Antifungal Delivery: A comprehensive review - Suyal, Pallavi; Dutta, Disha; Aslam, Ramsha; Bisht, Manoj (Journal of Neonatal Surgery, 2025)
Aim: The increasing prevalence of fungal infections and the rise of antifungal resistance necessitate innovative drug delivery strategies to enhance therapeutic efficacy and minimize toxicity. This review aims to provide a comprehensive overview of emerging lipid-based delivery systems—such as solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), liposomes, and lipid-drug conjugates—developed for efficient antifungal drug delivery. Methodology: A systematic literature search was conducted across databases including PubMed, Scopus, and ScienceDirect, focusing on studies published between 2005 and 2025. The selected articles were screened for relevance to lipid-based antifungal drug delivery, formulation strategies, physicochemical characteristics, in vitro/in vivo efficacy, and toxicity profiles. Comparative evaluation was performed to assess the advantages and limitations of each system. Results: Lipid-based formulations demonstrated superior drug encapsulation, improved solubility of poorly water-soluble antifungal agents (e.g., itraconazole, amphotericin B), sustained release profiles, and enhanced skin/mucosal penetration. Among these, NLCs and liposomes showed significant promise in reducing systemic toxicity and improving site-specific delivery. Novel hybrid and surface-functionalized lipid systems further enhanced antifungal selectivity and bioavailability, especially in dermal and mucosal applications. Conclusion: Emerging lipid-based delivery systems represent a transformative approach in antifungal therapy, overcoming the limitations of conventional formulations. Their ability to enhance pharmacokinetic profiles, target infected tissues, and reduce drug resistance makes them promising candidates for future clinical applications. However, further translational studies and regulatory validations are warranted to ensure large-scale applicability and patient safety.